Enabling East Asian Communities to Drive Local Development - Worl (Washington, DC, 2013)
Local development activities have profound impact on poor people's welfare. Communities and local governments interact closest to where people live and where essential public services are delivered, such as local transport, water supply, health and education. Vibrant local development requires productive, balanced interaction between empowered communities and capable and accountable local governments. For this interface to function best, well-organized, well-informed communities demand development results, holding local authorities to account and, through participation in decisions and oversight of public service delivery, ensure that those authorities remain effective and open to citizen input. In tandem, local governments supply the capacity to deliver services, reliable resources and a desire to meet local citizens' needs. As a vision for local development, the supply of and demand for effective and responsive government are well-matched. In section one, this report lays out the scope of CDD operations in East Asia and presents three frameworks for organizing them: according to local government context, sectoral scope, and primary development objectives. Organizing six results hypotheses according to a generic CDD results template; section two presents available evidence from East Asia's CDD experience. And section three summarizes lessons learned from this flagship effort.